The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1007/s40204-014-0032-9
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium corrosion particles do not interfere with the immune function of primary human and murine macrophages

Abstract: Magnesium is currently under investigation as a prospective biodegradable implant material. Biodegradation of magnesium causes a release of magnesium, hydroxide ions and hydrogen gas but it can also lead to the formation of particulate debris. Implant-derived particles may have immunotoxic effects. To investigate the influence of magnesium-derived particles on the immune functions of primary macrophages, up to 500 μg/ml magnesium or magnesium corrosion particles were added to the cell culture medium. No major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Prospective applications for degradable metallic implants in soft tissue are vascular stents to keep blood vessels open until newly formed vessels can overtake their function or in hard tissue, screws or nails to stabilize broken bones until the healing process is completed. Advantages of magnesium alloys that have been reported include bone regenerating, non‐inflammatory as well as antibacterial properties . Such inherent antibacterial activities of implants could antagonize the formation of antibiotic treatment‐resistant bacterial biofilm infections and would therefore be highly relevant .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prospective applications for degradable metallic implants in soft tissue are vascular stents to keep blood vessels open until newly formed vessels can overtake their function or in hard tissue, screws or nails to stabilize broken bones until the healing process is completed. Advantages of magnesium alloys that have been reported include bone regenerating, non‐inflammatory as well as antibacterial properties . Such inherent antibacterial activities of implants could antagonize the formation of antibiotic treatment‐resistant bacterial biofilm infections and would therefore be highly relevant .…”
Section: Introductionmentioning
confidence: 99%
“…Advantages of magnesium alloys that have been reported include bone regenerating, non-inflammatory as well as antibacterial properties. [4][5][6][7][8][9][10][11][12][13] Such inherent antibacterial activities of implants could antagonize the formation of antibiotic treatment-resistant bacterial biofilm infections and would therefore be highly relevant. 14,15 To simplify the analysis of the corrosion products, in this study pure magnesium was used.…”
Section: Introductionmentioning
confidence: 99%
“…However, inflammatory or cytotoxic alloy metal corrosion products could accumulate with time and lead to long‐term side effects such that this approach may have serious limitations . After an initial burst of corrosion, magnesium hydroxides as well as molecules from the biological environment such as phosphorus and calcium form a protective coating that slows down the subsequent corrosion process and improves the biological properties of magnesium‐based implants . Therefore, artificial coatings generated in vitro have been investigated to control the corrosion rate in particular during the critical time period immediately after implantation .…”
Section: Introductionmentioning
confidence: 99%
“…2,17 After an initial burst of corrosion, magnesium hydroxides as well as molecules from the biological environment such as phosphorus and calcium form a protective coating that slows down the subsequent corrosion process and improves the biological properties of magnesium-based implants. [18][19][20][21][22][23] Therefore, artificial coatings generated in vitro have been investigated to control the corrosion rate in particular during the critical time period immediately after implantation. [24][25][26][27][28][29] So far there has been no robust and efficacious coating reported that fulfills the expectations with regard to the absence of toxic components, efficacy and stability in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages could regulate the degradation of biomaterials by secreting proteolytic enzymes, matrix metalloproteinases and phagocytosis [ 42 , 43 ]. Macrophages maintained the ability of clearing intracellular mycobacterium segments via phagocytosis under an environment containing magnesium particles [ 44 ]. Our results further revealed the phagocytosis of macrophage could be only affected by high concentration extract of Mg-based alloy.…”
Section: Discussionmentioning
confidence: 99%